REVITALISASI KEBERPIHAKAN PROFESI ADVOKAT TERHADAP KLIEN YANG TIDAK MAMPU - Agus Nurudin (Faculty of Law, Universitas Diponegoro, 2012)
Revitalizing the role of advocate is very urgent now, so that its position is still worth mentioning as one of the elements of law enforcement, even as the front line in providing human rights protection, especially for people who can not afford to procedural law in court. The revitalization, especially on the function of an advocate role, the moral obligation to support a fair trial and right, position the community who can not afford equal before the law, provide free legal assistance to citizen who can not afford and using the law with a conscience.